2008
DOI: 10.4102/jsava.v79i3.262
|View full text |Cite
|
Sign up to set email alerts
|

Limb fracture during recovery from general anaesthesia : an often tragic complication of equine anaesthesia : clinical communication

Abstract: A 10-year-old Thoroughbred mare was presented for lameness of the left hindlimb as a result of an apical fracture of the lateral proximal sesamoid bone. The mare was ultimately euthanased after suffering catastrophic fractures of the 3rd and 4th metatarsal bones of the contra-lateral hindlimb during an uncoordinated attempt to rise during recovery from general anaesthesia after undergoing arthroscopic surgery. The case report focuses mostly on horse anaesthesia-related mortality, anaesthetic procedure in the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…When used alone, it can induce undesired effects such as muscular hypertonicity, myoclonus and convulsions (Nesgash et al, 2016). To minimize these side effects, ketamine is administered in combination with other drugs: benzodiazepines and alpha-2 agonists such as xylazine (Dzikiti et al, 2008;Ozkan et al, 2010). Ultra-short acting barbiturate e.g.…”
Section: Introductionmentioning
confidence: 99%
“…When used alone, it can induce undesired effects such as muscular hypertonicity, myoclonus and convulsions (Nesgash et al, 2016). To minimize these side effects, ketamine is administered in combination with other drugs: benzodiazepines and alpha-2 agonists such as xylazine (Dzikiti et al, 2008;Ozkan et al, 2010). Ultra-short acting barbiturate e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction of these attempts is essential for the prevention of accidents and increased safety during recovery from anesthesia because most injuries (e.g., fractures, articular dislocations, lacerations, wound dehiscence) occur during multiple and premature attempts to stand. [4][5][6][7][8][9][10][11] The longer recovery with the higher xylazine dose resulted from increased duration of sternal recumbency because the duration of lateral recumbency was similar between groups. These data suggested that 0.50 mg/kg xylazine is advantageous for prevention of trauma complications when recovery quality and number of attempts to stand are more critical than recovery duration.…”
Section: Discussionmentioning
confidence: 99%
“…Number of attempts to stand for G25 (4.0 AE 1.1) was greater than for G50 (1.1 AE 0.3; P ¼ .016). Total recovery score for G25 (median [range], 23 [18][19][20][21][22][23][24][25][26][27][28][29]) was higher than G50 (18 [10][11][12][13][14][15][16][17][18][19][20][21][22][23]; P ¼ .004). Overall attitude score (P ¼ .0007) and balance and coordination score (P < .0001) were higher for G25 (3 [3-5] and 3 [3][4][5], respectively) than G50 group (1 [1-3] and 1 [1-1], respectively; Table 1).…”
Section: Recovery Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…; Dzikiti et al. ). That Arabian horses, which exhibit more compulsive behaviours linked to anxiety or stress when stabled (Luescher et al.…”
Section: Introductionmentioning
confidence: 98%